Assessing the Intricate Balance of Intermolecular Interactions upon Self-Association of Intrinsically Disordered Proteins. Issue 3 (1st February 2019) - Rieloff, Ellen; Tully, Mark D.; Skepö, Marie
Abstract: Attractive interactions between intrinsically disordered proteins can be crucial for the functionality or, on the contrary, lead to the formation of harmful aggregates. For obtaining a molecular understanding of intrinsically disordered proteins and their interactions, computer simulations have proven to be a valuable complement to experiments. In this study, we present a coarse-grained model and its applications to a system dominated by attractive interactions, namely, the self-association of the saliva protein Statherin. SAXS experiments show that Statherin self-associates with increased protein concentration, and that both an increased temperature and a lower ionic strength decrease the size of the formed complexes. The model captures the observed trends and provides insight into the size distribution. Hydrophobic interaction is considered to be the major driving force of the self-association, while electrostatic repulsion represses the growth. In addition, the model suggests that the decrease of association number with increased temperature is of entropic origin. Graphical Abstract: Highlights: Statherin self-associates with increased protein concentration. The self-association is affected by temperature, salt, and urea. Hydrophobic interaction is considered the major driving force. A coarse-grained model captures observed trends and provides insight into size distribution. The self-association is an intricate balance between intermolecular interactions and entropy.